Capital Structure and Investment Decisions on Firm Value with Profitability as a Moderator - Syamsudin, S; etiadi, Iwan S; Santoso, Dwi; Setiany, Erna (Universitas Muhammadiyah Surakarta, 2020)
This study aims to examine the effect of capital structure and investment decisions on firm value with profitability as a moderating variable. Capital structure is measured by debt to equity ratio, investment decisions are measured by priceearnings ratio, profitability is measured by Return on Assets and firm value is measured by Tobin’s Q. The analytical tool used is multiple linear regression analysis to test the direct effect between variables and the Moderated Regression Analysis is used to test the effect of moderating variables. The sampling method uses the purposive sampling technique. The research sample amounted to 18 LQ45 non-financial sector companies listed on the Indonesia Stock Exchange from 2013 to 2017. The results of the study prove that capital structure, investment decisions, and profitability have a significant positive effect on firm value. Profitability is proven to be able to moderate the influence of capital structure and investment decisions on firm value. The implications of this study indicate that profitability has an important role in realizing the dimensions of the company’s growth prospects that have an impact on increasing corporate value.